Between Constitutional Commitment and Policy Reality: An Analysis of Poverty Alleviation in Aceh - Nanda Herijal Putra; Muhammad Suhaili Sufyan (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2026)
Poverty in Aceh continues to present a serious obstacle to the achievement of social welfare in Indonesia. Although the 1945 Constitution assigns the state a clear responsibility to ensure social justice and equitable prosperity, significant disparities remain in people’s access to education, healthcare, employment opportunities, and economic resources. This situation indicates a persistent mismatch between constitutional ideals and the realities of public policy implementation. This study departs from the limited body of literature that connects constitutional law perspectives with public policy theory, particularly the work of Thomas R. Dye, in explaining structural poverty. Previous studies generally treat constitutional analysis and policy evaluation separately, which limits a more integrated understanding of how constitutional mandates are translated into policy choices. The study aims to examine structural poverty alleviation as a constitutional responsibility of the state through Thomas R. Dye’s public policy perspective, with specific attention to the concept of government choice in shaping policy directions and implementation. A normative legal research method is applied, using statutory, conceptual, and policy approaches. The data are collected through library research and analyzed qualitatively. The findings suggest that, in Dye’s framework, structural poverty is shaped less by resource constraints and more by political and institutional government choices regarding agenda setting, resource allocation, and policy priorities. In Indonesia, poverty reduction policies are still largely oriented toward short-term social assistance, while structural reforms that address inequality at its roots remain limited. This condition results in a gap between constitutional commitments and actual policy performance. The study concludes that a realignment of policy choices is necessary to better reflect constitutional obligations through more structural, inclusive, and justice-oriented governance within the welfare state framework.